CD44 plays a critical role in regulating diet-induced adipose inflammation, hepatic steatosis, and insulin resistance. - Hong Soon Kang; Grace Liao; Laura M DeGraff; Kevin Gerrish; Carl D Bortner; Stavros Garantziotis; Anton M Jetten (PLoS ONE)
CD44 is a multifunctional membrane receptor implicated in the regulation of several biological processes, including inflammation. CD44 expression is elevated in liver and white adipose tissue (WAT) during obesity suggesting a possible regulatory role for CD44 in metabolic syndrome. To study this hypothesis, we examined the effect of the loss of CD44 expression on the development of various features of metabolic syndrome using CD44 null mice. Our study demonstrates that CD44-deficient mice (CD44KO) exhibit a significantly reduced susceptibility to the development of high fat-diet (HFD)-induced hepatic steatosis, WAT-associated inflammation, and insulin resistance. The decreased expression of genes involved in fatty acid synthesis and transport (Fasn and Cd36), de novo triglyceride synthesis (Mogat1), and triglyceride accumulation (Cidea, Cidec) appears in part responsible for the reduced hepatic lipid accumulation in CD44KO(HFD) mice. In addition, the expression of various inflammatory and cell matrix genes, including several chemokines and its receptors, osteopontin, and several matrix metalloproteinases and collagen genes was greatly diminished in CD44KO(HFD) liver consistent with reduced inflammation and fibrogenesis. In contrast, lipid accumulation was significantly increased in CD44KO(HFD) WAT, whereas inflammation as indicated by the reduced infiltration of macrophages and expression of macrophage marker genes, was significantly diminished in WAT of CD44KO(HFD) mice compared to WT(HFD) mice. CD44KO(HFD) mice remained considerably more insulin sensitive and glucose tolerant than WT(HFD) mice and exhibited lower blood insulin levels. Our study indicates that CD44 plays a critical role in regulating several aspects of metabolic syndrome and may provide a new therapeutic target in the management of insulin resistance.